(untitled) (Journal of Information Technologies in Education (ITE), 2011)
In this article the mathematical model of prognostication of action of students of higher educational establishments is built and investigated on the basis of the laws of fuzzy logic.The results of students’ questionnaire of higher educational establishments became the informative base of the research. The functions of belonging as for the finding the levels of student action are presented.Research results enabled ranking the students on nine levels of action, that provide the prognostication of students’ actions and the influence on the state of affairs on the labour-market.